Public administration and civil service reforms in Nigeria - Olaopa, Tunji (Ibadan, Nigeria: University Press Plc, 2010)
This book explores the main theoritical and conceptual issues in public administration, it also draws on historical and experimental data to discuss various dimensions - political, structural and attidunal - of the dysfunctions of the Nigerian civil service, particularly since the late 1970s to this period.
Includes bibliographical references (p. 302-319) and index.
lje 3/8/13, ijb 06/02/2019
Loan
Keywords: Public administration; Bureaucracy; Civil Service